OvinOralOme: Ovis aries oral proteome database - Esteves, E. (2015)
Introduction: Tools to store and catalog proteins identified in proteome surveys of tissues from subjects representing different physiological and pathological states are powerful instruments to integrate published information. Much of the information on molecular mechanisms can be generated using bioinformatics strategies powered by this tools. Within the scope of previous projects a database named OralOme was built, dedicated to the storage of all the information on the proteins of the human oral cavity. This database is available through the web interface OralCard. Objective: The present study aims the development of a database transferring the methodology used in humans to the storage and cataloguing of the proteins present in the oral cavity and other tissues of Ovis aries. This database will be essential to develop diagnosis methods to be applied to living animals targeting the most prevalent diseases affecting the flocks in Serra da Estrela region. Methods: The development of this database involves the manual compilation and review of the proteins, identified in different studies, relative to Ovis aries, with the annotation of the sample characterization and proteomics techniques used. Results: The database resultant from this work is called OvinOralOme and includes proteins identified in proteomic and directed studies, published in the scientific literature from 2000 to 2013. Conclusion: The creation of OvinOralOme is a valuable instrument for the underlying several pathologies of these animals.